Evaluación de la inclusión de un suplemento orgánico proteico a base de suero de leche en la alimentación de pollos camperos de 15 días de edad - Villota Valencia, Katerine Juleidy (2022)
Poultry production is one of the most relevant economic activities worldwide, however, the high production costs derived from feeding birds are a great conditioning factor for said activity, and the reality of Ecuador is the same, mainly in the raising of free-range chickens, due to causes such as the reduced alternatives of food supplements added to the scarce knowledge on the part of producers about protein alternatives from the dairy industry. In this way, a solution to this problem is the use of whey as an organic protein source that, thanks to its high nutritional content, allows obtaining better production rates. The main objective of the research was to evaluate the effect of the inclusion of an organic protein supplement based on whey in the feeding of 15-day-old free-range chickens. The experimental site for the study was the 'Rancho Fátima' farm, located in the Bolívar canton, in the province of Carchi. For the execution of the experiment, a completely randomized design (DCA) was used, distributed in 4 treatments and 3 repetitions, having a total of 12 experimental units each with 6 birds, and the supplied whey was considered as a study factor in doses of 15%, 30% and 45% in the drinking water according to the requirements of the animals. The use of whey allowed obtaining excellent zootechnical parameters, mainly in terms of daily weight gain, where values of 51.75 grams were reached corresponding to the T3 treatment with 45% addition of this supplement, so that the results obtained allow us to assert that This by-product is a very good food alternative for free-range chickens since, in addition to improving production rates, it contributes to the economy of the producer during the productive cycle of the birds, favoring the sustainable development of free-range poultry.